One-Pot Synthesis of Tetrazole–Triazole Bis-Heterocycles via Ugi–Azide Reaction - Fidel Rodriguez-Lopez; Carlos Zárate-Hernández; Manuel A. Rentería-Gómez; Rocío Gámez-Montaño (Chemistry Proceedings)
Bioisosteres of amide bonds such as 4,5-disubstituted-1,2,3-triazoles (4,5-DS-1,2,3-Ts) and 1,5-disubstituted tetrazoles (1,5-DST) are present in compounds with important biological activities like those that are antineoplastic, antibacterial, antifungal, and antiparasitic, and antifungal, antiparasitic, antiviral, and anti-inflammatory. In the present work, we describe the synthesis of tetrazole–triazole bis-heterocycles via the Ugi–Azide strategy. The target molecules were synthesized with moderate yields, under mild conditions, employing 2H-1,2,3-triazole aldehyde as an input.